Three new species of the genus Ripeacma (Lepidoptera: Oecophoridae) from China - Yin, Aihui; Wang, Shuxia (Zootaxa, 2013)
Three new species of the genus Ripeacma Moriuti, Saito et Lewvanich, 1985 are described based on specimens collected in China: R. quadridigitata sp. nov. from Guizhou, R. damingshana sp. nov. from Guangxi, and R. magnihamata sp. nov. from Fujian. Images of adults and genitalia are provided.